P95 Growth and Nutrition in Ataxia Telangiectasia. (12th November 2015) - Stewart, EL; Tooke, A; Pasalodos, S; Suri, M; Bush, A; Bhatt, J
Abstract : Background: Ataxia telangiectasia (A-T) is a rare multisystem disease with high early mortality from lung disease and cancer. Nutritional failure adversely impacts outcomes in many respiratory diseases. Several factors influence nutrition in children with A-T including catabolism during recurrent infections and inadequate oral intake (fatigue, difficulties with chewing or swallowing, poor appetite, and nausea due to medications). We hypothesised that children with A-T have progressive growth failure. Methods: Data was collected prospectively on weight, height and body mass index (BMI) at the national paediatric A-T specialist clinic in Nottingham. Adequacy and safety of oral intake was assessed. Nutritional advice was given at each multidisciplinary review. Results: 92 children (46 girls) (33 once, 37 twice, 20 thrice, 1 child four times and 1 child 5 times) had 176 measurements since 2009. Median (range) age was 9.2 (1.5 to 18.4) years. Weight, height and BMI Z-scores were respectively -0.84 (-8.34 to 3.58), -0.98 (-5.85 to 3.66) and -0.24 (-4.45 to 2.75). Weight, height and BMI Z-scores inexorably declined over time. 10 children had a gastrostomy, with longitudinal data available for 8. 87.5% of these children improved their BMI Z-score with time. 18.5% (17) children were considered wasted (BMI Z-score ≤-2). All of these children were above 8 years old. Longitudinal data was available for 14 wasted children. 6 of these children had a gastrostomy inserted and 5 then improved their Z-score. Of the remaining 8 children without gastrostomy, 7 (87.5%) continued to decrease their BMI over time despite dietary advice to fortify food or add in supplements. Conclusions: There is a remorseless decline in growth over time. There is an urgent need for new strategies, including an understanding of why growth falters. Undernutrition adversely affects acute and chronic lung health. Outcomes for late gastrostomy insertion in AT are poor ( Lefton Greif OJRD;2011;210 ). We suggest early proactive consideration of gastrostomy from age 8 years upwards in order to prevent respiratory deterioration.